National Survey of Pharmacy Leadership at Ministry of Health in Saudi Arabia: Working Environment - Alomi, Yousef Ahmed; Abdulmohsen Albaz, Modhi; AlMuhraj, Wejdan Fawzan; AlKharji, Mashael Yasser; Alshuraym, Norah Rushud (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the national survey of pharmacy leadership at the Ministry of Health with emphasis on pharmacy Working Environment. Methods: It is a ninety days cross-sectional national survey of pharmacy leadership practice at Ministry of Health. The survey modified from self-assessment of 360 leadership and with pharmacy leadership literature. The electronic format of the survey through the survey monkey system and distributed through emails. All analysis is done through the survey monkey system. The survey divided into several parts for analysis, and discussion. Part one: practice management, part two: planning and organizations, part three: communications strategies, part four: problem-solving and decision making, part five: performances management, part six; working environment, and part seven: professional development. The study explored the part number six: National Survey of Pharmacy leadership: Working Environment. Results: The survey distributed to one hundred hospitals, the response rate, was forty-two hospitals (42%) with seventy-pharmacy leaders. The gender distribution of responders was Male 43 (63.24%) and female 25 (36.76%) while the nationality was Saudi 69 (98.57%) and non-Saudi 1 (1.43%). The majority of pharmacy leadership described the current environment as work culture A 24 (38.1%) and work culture C 23 (36.5%). The most of them preferred work culture B 20 (31.25%) and Work culture A 19 (29.69%). The average score Cultural Awareness skills were 2.48 (82.65%) with the highest score was Full respect for people who are not sharing the same region 2.73 (90.99%). The majority of pharmacy leaders agreed the higher Management within the organization recognizes strong job performance 31 (46.27%), the Employees proactively identify future challenges and opportunities 33 (53.23%), and Employees in my organization willingly accept change 31 (47.69%). Most of the pharmacy leaders (70%) though that is the maximum time should become pharmacy leader at his or her position four to five years. Conclusion: The pharmacy leaders had some challenges with workplace environment. Targeting to review pharmacy workplace and implement the new model of the culture environment is required. Also, further with another a detail investigation of pharmacy workplace environment is highly recommended at healthcare organizations in Saudi Arabia.
Keywords: Pharmacy leadership; Working environment; Ministry of health; Saudi arabia